Visual Disclosure dan Pelaporan Keuangan: Tinjauan Literatur Sistematis atas Studi Empiris (2015–2025) - Amalina Nur Arifah; Arief Rahman (Owner : Riset dan Jurnal Akuntansi, 2026)
Financial reporting has undergone significant transformation with the integration of visual elements as a means of conveying complex information. This study aims to conduct a systematic literature review of research trends in visual disclosure within the financial reporting context. Following the PRISMA 2020 protocol, 51 empirical articles from the Scopus and Web of Science databases published between 2015 and 2025 were analyzed using systematic content analysis with Nvivo and bibliometric mapping with VOSviewer. The findings reveal a dominance of quantitative and computational approaches, with Graph Theory, Machine Learning, and Statistical Models as the main theoretical foundations. Methodologically, Simulation & Mathematical Modeling and Computational Experiments dominate the research. The study also identifies strong interdisciplinary characteristics involving computer science, statistics, and business, although deep integration among these perspectives remains limited. Furthermore, research tends to focus on tool development (tool-centric) rather than user understanding (user-centric), with a high reliance on secondary data. Bibliometric analysis with VOSviewer confirms these thematic patterns, showing strong keyword co-occurrence networks between graph, model, analysis, and data. In conclusion, the field of visual disclosure research requires better integration between technical innovation and contextual user understanding, the development of more holistic theoretical frameworks, and the expansion of research scope to more diverse organizational contexts through mixed methods and more genuine interdisciplinary collaboration.